Hospitality to Others Rooted in an Ecclesiology of the Baptized People of God - Shaw, C. Pierson (Toronto journal of theology, 2019)
Video Abstract Hospitality to Others Rooted in an Ecclesiology of the Baptized People of God Download Original Video (35.0 MB)Get the Flash Player to see this video.addFlashMovie('d17447e138','/doi/video_low/10.3138/tjt.2018-0114/SHAW_VIDEO_ABSTRACT_S.flv') If the Church is considered to be an assembly of the baptized people of Christ's body, then that structure necessarily compels members of that body to be mindful of the plight of the displaced: refugees, immigrants, sojourners, trafficked people, strangers, victims of crisis, marginalized migrants, and, in fact, anyone seeking justice and safety. In this context, there is a biblical imperative to action, compelling baptized people to show justice and mercy in times of crises. This imperative often gets overlooked, especially in recent days with the migrant crises created by the Trump administration with respect to the southern US border. This article maps out different global/historical situations of immigrant crises to provide a context for the current situation. It offers background on the contempt shown by the US president's migrant policy and then correlates and advances biblical imperatives, especially as given by the New Testament and along Pauline lines. It argues for spelling out a reminder: government is an agent of God in the natural law order. And, from a Christian perspective, Church leaders and baptized people of God have an obligation to live out a call to love in the form of an ecclesiology of hospitality. That is, God's covenant with the baptized people implies an enabling directive to the Church, its leaders, and the body of Christ to advocate for migrants and victims amid the escalating crises created by government policies that show contempt for migrants and their families.